Scalable off-grid energy services enabled by IoT: A case study of BBOXX SMART Solar. (October 2017) - Bisaga, Iwona; Puźniak-Holford, Nathan; Grealish, Ashley; Baker-Brian, Christopher; Parikh, Priti
Abstract: This case study intends to show how Internet of Things (IoT) technology can be used to tackle development challenges by using the case study of BBOXX- a Solar Home Systems provider operating in South-Western Kenya and across Rwanda, and its SMART Solar platform applied to nearly 20, 000 currently active systems. It aims to highlight the benefits of such technology to its users and how it can be utilised to create scalable business models for energy access through improved customer understanding. However, it also shows the difficulties in designing, developing and deploying appropriate technologies in an affordable and impactful way. Similar applications in the water sector are briefly looked at to further explore the potential and the challenges of IoT technologies in driving social and economic development. The case study raises ethical questions about the storage, collection and sharing of data and explores whether the data protection models prevalent in the developed world are applicable in a development context. It offers ideas for future research and policy recommendations, pointing to the need of including financial, socio-economic and ethical considerations in the processes of innovative solutions development. Highlights: Internet of Things (IoT) technologies can help create scalable business models. Off-grid energy usage data is used for improved customer understanding. Data cost, mobile network reliability and high hardware costs pose challenges. Ethical questions around energy use data collection, storage and sharing are raised. More inclusive public-private collaboration to create policy frameworks is proposed.